Safety and efficacy of RNA vaccines: State of the art - A. V. Blagov; A. A. Bukaeva; V. V. Makarov; Z. V. Bochkaeva (Медицинская иммунология, 2021)
This review describes principles of action and the method of delivery of mRNA molecules into cells, as well as some of developed RNA vaccines and the results obtained in their study, though they have not been authorized for use yet. In addition, the review discusses efficacy and safety proved for RNA vaccines registered for COVID-19 prevention at the time of writing. The development, clinical trials and market launch of RNA vaccines for mass immunization in a few months can be considered one of the major breakthroughs in pharmacology over the past year. Despite of all seemingly indisputable advantages, none of RNA vaccines had reached Phase III of clinical trials since the moment of its discovery in 1993 until last year. The first experience of the successful use of mRNA vaccines was back in the 90s of the last century, when vaccination of mice with liposomes encoding an antigen-encoding mRNA was found to initiate specific immune response in mice. However, in these years, the method did not find application, due to the toxicity of lipids used. Subsequently, a large number of attempts have been made to develop vaccines against other viral infections, including Zika virus, Dengue virus, Ebola virus, cytomegalovirus, influenza virus and others. Despite the importance for preventing the spread of these diseases, the development of a vaccine preparation is a rather lengthy process, and final success is not guaranteed. However, the COVID-19 pandemic has become speeded the development of mRNA vaccines up.At the time of writing the review, two mRNA-based vaccines have been registered only in the world, both, BNT162b2 and mRNA-1273, were against COVID-19. Their effectiveness and safety are still actively studied. Moreover, it took less than a year for new strains of SARS-CoV-2 to appear, and the efficiency of vaccines against them was found to be lower than against the reference pathogen variant. Considering that the three new strains of SARS-CoV-2, “British”, “African” and “Brazilian”, are rapidly spreading in the world, the first results of efficiency evaluation of vaccines against them have already been published. One may expect that, considering mutations in these strains, the BNT162b2 and mRNA-1273 vaccines will remain effective against the “British” strain, but their protective properties are greatly weakened against the “African” variant.